Comparison on the cell abundance of benthic dinoflagellates in macrophytes and water column collected from open coastal waters and semi-enclosed lagoon - Normawaty Mohammad-Noor,; Asilah Al-Has,; Shahbudin Saad,; Than Aung, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Benthic dinoflagellates are known to occur in the water column. The reason they can be found in different parts of the ecosystem is not clear. This study aims to determine the species and the cell abundance of benthic dinoflagellates in the water column and macrophytes collected from two different locations i.e. semi-enclosed lagoon and open coastal waters. The physico-chemical parameters (temperature, salinity, pH, dissolved oxygen) and nutrients (nitrate and phosphate) were determined. Results showed that in the lagoon, the most abundant dinoflagellate species on the macrophytes was also the most abundant dinoflagellate species in the water column. The species that dominated the water column and marophytes in the lagoon was Bysmatrum caponii. In the coastal area the trend was not clear. Coolia dominated the macrophytes whereas Peridinium quinquecorne dominated the water column. The physico-chemical parameters determined were similar at both sites except for nutrients. Results show that type of substrates and different geomorphology effects benthic dinoflagellates cell abundance in the macrophytes and water column.